Economic Growth And Public Expendture: Country Specific Test Of The Armey Curve Hypothesis In Nigeria And Ghana - Asogwa, Fredrick Onyebuchi; Okwudili, Ajibo Stephen; Urama, Musa Sherrif (Advances in Social Sciences Research Journal, 2019)
The massive spending programs adopted by many countries around the world in response to the economic crisis of 2008 have drawn renewed attention to the role of government in an economy. Studies of the relationship between government size and economic growth in most countries of the world have come up with a wide range of estimates of the optimal or growth maximizing size of government, ranging between 15 to 30% of Gross Domestic Product (GDP). These studies discovered the optimal size of government for the various countries using the theoretical framework of Armey Curve Hypothesis which theorized the existence of an optimal size of government that maximizes growth.Over the past year(s), government’s aggregate expenditure has been less than its aggregate expenditure the present year(s) in Nigeria and Ghana. This has made the government size of these economies big enough to command a significant economic growth in these countries, but this is not the case in these countries. This work adopted a concave parabolic model from the origin which portrays the Armey curve model to empirically validate not only the existence of Armey curve hypothesis but also to fond the optimizing government expenditure of Ghana and Nigeria, using time series data from 1981 to 2016. The result showed that Armey curve hypothesis exists both in Nigeria and Ghana. However, the result shows a strong statistical influence of Armey hypothesis in Nigeria than in Ghana. In line with the main objective of the study, the optimal size of the government was found to be 12.5% and 7.3% of the gross domestic product in Nigeria and Ghana respectively. The implication is that Government of Nigeria and Ghana should spend 12.5% and 7.3% respectively, of her gross domestic product (GDP) to attain the optimal growth of ₦3 Trillion Naira and ₡4.3 million respectively. The researcher recommends that these governments should cut down their expenditure to the optimizing size of their governments so as to grow effectively and efficiently which is a macroeconomic goal of every economy.